Notice of Retraction: The characteristics of TB6600 motor driver in producing optimal movement for the Nema23 stepper motor on CNC machine - M. Khairudin; R. Asnawi; A. Shah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This article has been retracted by the publisher. -----------------------------------------------------------------------This article has been retracted at the request of the Authors. The editors and authors have jointly made the decision to retract the paper. Reasonable effort should be made to remove references to this paper.-----------------------------------------------------------------------This study describes the use of the TB6600 motor driver for the stepper motor on CNC machine. Based on the analysis of the performance of the TB6600 motor driver, in order to produce an optimal stepper motor of Nema23 on CNC machine, three stepper motors are needed as the CNC engine drives for the X, Y and Z axeo be connected to the TB6600 motor driver. The motor is then controlled by Raspberry Pi via Mach3 Interface Board of Breakout Board. The softness of motion and safe working temperature for the stepper motor of Nema23 on CNC machine are obtained by varying the control of the micro-step switches and controlling current switches. The results show that 32 steps of micro-step control produce smoother resonance and movement than smaller micro-steps. In addition, the current control of 1 A generates the best motor driver output with a lower temperature for all three stepper motors.